Consistency between national guidelines and reported practice for reducing the risk of catheter-related infection in british picus. (4th April 2011) - Harron, K L; Ramachandra, G; Mok, Q; Gilbert, R
Abstract : Objectives: Optimal strategies for reducing catheter-related blood stream infection (CR-BSI) differ for adults and children, yet national guidelines do not make child-specific recommendations. We determined consistency between guidelines and reported practice in Paediatric Intensive Care Units (PICUs). Methods: We compared national guidelines and reported practice in PICUs for seven interventions to reduce CR-BSI, ascertained by a national survey of all 25 PICUs in Britain in 2009. For each intervention, we determined whether best available evidence explained inconsistencies between guidelines and reported practice. Results: 24 of 25 PICUs (96%) responded. Practice diverged from guidelines for 2/3 interventions that required child-specific evidence. (i) Femoral sites were used for emergency patients instead of subclavian/jugular sites in 18 PICUs – consistent with evidence regarding improved safety and ease of insertion at femoral sites and lack of Randomised controlled trial (RCT) evidence favouring subclavian/jugular sites in children. (ii) Use antimicrobial-impregnated CVCs for high-risk patients. Three PICUs used heparin-bonded CVCs exclusively; none used antimicrobial-impregnated CVCs – consistent with RCTs showing large benefits of heparin-bonded CVCs for children regardless of risk-status and no RCTs of antibiotic-impregnated CVCs in children. Practice reflected guidelines for (iii) use of 2% chlorhexidine for skin preparation (used in 20 PICUs), consistent with an RCT in neonates. Practice diverged from guidelines for 3/4 interventions not requiring child-specific evidence. (iv) Administration sets were replaced as recommended in 21 PICUs. (v) 2% chlorhexidine was used for cleaning hubs for CVC access in only 12 PICUs – a recommendation based on weak evidence. (vi) 23 PICUs reported CVC care training sessions for nurses; only nine PICUs reported CVC insertion training sessions for doctors – despite strong observational evidence supporting training. (vii) Only eight PICUs reported regular monitoring of CR-BSI – despite strong RCT evidence for benefits of audit and feedback, weak observational evidence for reducing infection through surveillance, and strong arguments for monitoring outcomes of multi-faceted intervention bundles. Conclusions: Guidelines should address paediatric practice specifically and explicitly assess both quality of evidence and strength of recommendations. PICU teams could improve adherence to CVC care guidelines, but training of doctors and monitoring infection need to be implemented at an organisational level.